Perbandingan Kinerja Keuangan Menggunakan Rasio Likuiditas, Solvabilitas, Aktivitas, dan Profitabilitas Pada Perusahaan Sub Sektor Rokok di BEI Tahun 2016-2023 - Damayani, Dila; Murdiyanto, Edi; Mahaputra, Agung Pambudi (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze and determine whether or not there are differences in financial performance between cigarette sub-sector companies listed on the Indonesia Stock Exchange in 2016 - 2023. This type of research uses quantitative research with a comparative method. Sampling was carried out using the purposive sampling method and four companies were obtained. The data used in this study are secondary data using the company's annual financial reports. Hypothesis testing was carried out using the Kruskal-Wallis test for non-normally distributed data and the One-Way ANOVA test for normally distributed data. The results of the study indicate that there are significant differences between the financial performance of PT HM Sampoerna Tbk, PT Gudang Garam Tbk, PT Wismilak Inti Makmur Tbk, and PT Indonesian Tobacco Tbk as seen from the liquidity ratio (Current Ratio), solvency ratio (Debt To Asset Ratio), activity ratio (Total Asset Turn Over), and profitability ratio (Return On Asset).